2021
DOI: 10.18608/jla.2021.7230
|View full text |Cite
|
Sign up to set email alerts
|

Examining Student Regulation of Collaborative, Computational, Problem-Solving Processes in Open-Ended Learning Environments

Abstract: The integration of computational modelling in science classrooms provides a unique opportunity to promote key 21st century skills including computational thinking (CT) and collaboration. The open-ended, problem-solving nature of the task requires groups to grapple with the combination of two domains (science and computing) as they collaboratively construct computational models. While this approach has produced significant learning gains for students in both science and CT in K–12 settings, the collaborative le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 84 publications
1
14
0
Order By: Relevance
“…A study that examined different methods for assessing middle school students' use of evidence and systems thinking was coded as measuring learning (Ahn et al, 2021). Two studies that examined children's dialogue during collaborative problem solving were both coded as measuring learning (Emara et al, 2021;Ma et al, 2022). For readers who are skeptical of our findings, rather than presume that we've mischaracterized a learning-oriented literature, we recommend reviewing the article list, and our associated codes, and drawing your own conclusions from the data, which we've made public at https://osf.io/tzhva/.…”
Section: Discussionmentioning
confidence: 99%
“…A study that examined different methods for assessing middle school students' use of evidence and systems thinking was coded as measuring learning (Ahn et al, 2021). Two studies that examined children's dialogue during collaborative problem solving were both coded as measuring learning (Emara et al, 2021;Ma et al, 2022). For readers who are skeptical of our findings, rather than presume that we've mischaracterized a learning-oriented literature, we recommend reviewing the article list, and our associated codes, and drawing your own conclusions from the data, which we've made public at https://osf.io/tzhva/.…”
Section: Discussionmentioning
confidence: 99%
“…It has increased the potential for self-directed learning and social learning online (Martin et al, 2016). The C2STEM modules provide students with the opportunities to a) explore resource-intensive processes, such as trial and error, to more systematic processes, such as debugging model errors by leveraging data tools, and b) learn from each other using socially shared regulation and productive collaboration (Emara et al, 2021). A study by showed that educational technologies that combine standalone and embedded learning analytics help support blended learning by balancing teacher-led instructions with class-paced and individually-paced practices.…”
Section: Impacts On Studentsmentioning
confidence: 99%
“…In the third article, Emara, Hutchins, Grover, Snyder, and Biswas (2021) present a framework for analyzing rich collaboration data. They suggest that collaboration analytics can provide a better understanding of socially shared regulation (SSR) processes by capturing collaborative dialogue, log files, and task scores.…”
Section: Summary Of Papersmentioning
confidence: 99%